2002
DOI: 10.1038/nm754
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Notch-1 signaling maintains the neoplastic phenotype in human Ras-transformed cells

Abstract: Truncated Notch receptors have transforming activity in vitro and in vivo. However, the role of wild-type Notch signaling in neoplastic transformation remains unclear. Ras signaling is deregulated in a large fraction of human malignancies and is a major target for the development of novel cancer treatments. We show that oncogenic Ras activates Notch signaling and that wild-type Notch-1 is necessary to maintain the neoplastic phenotype in Ras-transformed human cells in vitro and in vivo. Oncogenic Ras increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
406
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(430 citation statements)
references
References 44 publications
19
406
2
3
Order By: Relevance
“…23 BxPC-3 cells were transfected with Notch-1 siRNA and siRNA control, respectively, using Lipofectamine 2000. BxPC-3 cells were stably transfected with human Notch-1 ICN or vector alone (pcDNA3) and maintained under neomycin selection.…”
Section: Plasmids and Transfectionsmentioning
confidence: 99%
“…23 BxPC-3 cells were transfected with Notch-1 siRNA and siRNA control, respectively, using Lipofectamine 2000. BxPC-3 cells were stably transfected with human Notch-1 ICN or vector alone (pcDNA3) and maintained under neomycin selection.…”
Section: Plasmids and Transfectionsmentioning
confidence: 99%
“…For example, in T-cell leukaemia it was shown that Notch-induced transformation required the activation of MAP kinase and PI-3 kinase activity (Fitzgerald et al, 2000). Conversely, it was shown that activation of Notch signalling was an obligate step in Ras-induced transformation in an experimental system using human fibroblasts (Weijzen et al, 2002). However, we only detected very modest activation of the ERK pathway upon VPA treatment (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…Abundant evidence indicates that Notch1 is involved in the angiogenesis and tumorigenesis of various types of malignancy. It has been revealed previously that Notch1 signaling is the convergence point of numerous signaling pathways (23). The dysfunction of Notch1 may inhibit cell differentiation, resulting in the malignant transformation of undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%